Improving ride comfort of straddle-type monorail vehicle with single-axle bogie by active suspension. (November 2021) - Du, Zixue; Xin, Liang; Yang, Zhen; Xu, Zhouzhou
This article is concerned with improving the ride comfort of straddle-type monorail vehicles with single-axle bogies by using electro-hydraulic actuator active suspension, which is a new research field. Based on the 15-DOF dynamic model of straddle-type monorail vehicle with single-axle bogie, the model of electro-hydraulic actuator is established, and the adaptive neural fuzzy inference system proportional–integral–differential (adaptive fuzzy inference system proportional–integral–differential) is designed. The simulink results show that the adaptive fuzzy inference system proportional–integral–differential control active suspension can effectively reduce the root mean square value and peak value of the lateral acceleration, vertical acceleration, roll angle acceleration, pitch angle acceleration, and yaw angle acceleration of monorail vehicles compared with the passive suspension. The active suspension of electro-hydraulic actuator can effectively improve ride comfort of the straddle monorail with single-axle bogie.